Association of multi-metals with the risk of hypertension and the interaction with obesity: A cross-sectional study in China - Wu, Shan; Li, Lvrong; Ji, Guiyuan; Xing, Xiaohui; Li, Jiajie; Ma, Anping; Wei, Yuan; Zhao, Dongwei; Huang, Huimin; Ma, Wenjun; Wu, Banghua; Dong, Ming; et al. (Frontiers in Public Health, 2023)
Background Environmental exposure to multiple metals have been inconsistently associated with hypertension. Obesity is an important independent risk factor for hypertension, and few studies have assessed the interaction between obesity and metals in this context. We aimed to clarify their association and interaction. Methods This cross-sectional study included 3,063 adults from 11 districts or counties, Guangdong. We measured the whole blood levels of 13 metals and used multipollutant-based statistical methods to analyze the association of metals with hypertension. The interaction between metals and obesity on hypertension was assessed on additive and multiplicative scales. Results Four metals (manganese, arsenic, cadmium, and lead) were significantly associated with hypertension risk, five metals (manganese, zinc, arsenic, cadmium, and lead) were related to elevated SBP levels, five metals (manganese, zinc, selenium, cadmium, and lead) were associated with elevated DBP levels in single-metal model. Manganese remained significantly related to hypertension risk [odds ratio, 1.35 (1.02–1.78)] after adjusting for these four metals. Significant positive dose-response relationships between manganese, arsenic, cadmium, lead and hypertension risk were observed (P for overall < 0.001, P for non-linearity > 0.05). Compared with those in the lowest quartile, participants in the highest manganese quartile had a 2.83 mmHg (95% Cl: 0.71–4.96) (PFDR = 0.040) higher level of SBP. Individuals in the highest quartiles of zinc and lead had a 1.45 mmHg (0.10–2.81) (PFDR = 0.033) and 2.06 mmHg (0.59–3.53) (PFDR = 0.020) higher level of DBP, respectively. The negative interactions between cadmium, lead and obesity influences hypertension risk. BKMR analysis showed a significant joint effect of manganese, arsenic, cadmium and lead on hypertension when the concentrations of four metals were at or above their 55th percentile compared to their median values. Conclusions The combined effect of four metals (manganese, arsenic, cadmium and lead) were associated with the prevalence of hypertension. Potential interaction effects of cadmium, lead and obesity on hypertension risk may exist. Further cohort studies in larger population are needed to clarify these findings.